(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research has purpose to analyze (i) the influence of oil prices, profitability and banks deposit on Islamic banks growth. (ii) the influence of Islamic banks growth on economic growth. The data for this study were collected from secondary data of the 105 Islamic banks from 24 countries. This research was conducted with the period of 10 years from 2007 to 2016, therefore this method using panel data regression. The result of panel data regression with fixed effect model consisted of the variable of oil prices, profitability, bank deposit have a significant positive effect on Islamic banks growth. The other results of panel data regression with fixed effect model consisted of the variable of islamic banks growth have a significant positive effect on economic growth. The results of this study consistent with the results of previous research. This means that the high growth of Islamic banking can increase a country’s economic growth. This study gives results that can be used as reinforcement from previous studies. This research is the first research that study on the effect of the Islamic banking growth while affecting economic growth in thr World. Therefore, government intervention is needed to maintain the stability of Islamic banking and good international relations are needed to keep oil price stable.